2016
DOI: 10.18632/oncotarget.9021
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of exosome-associated microRNA panels and in vivo environment to predict drug resistance for patients with multiple myeloma

Abstract: Multiple myeloma (MM) is the second most common hematologic neoplasms and an appropriate in vivo environment for myeloma cells has potential implications for initiation, progression, and metastasis of MM. Exosomes, entities carrying microRNAs (miRNAs) to target locations, participate in the cross-talk between myeloma cells and nonmalignant components of the in vivo environment. This study disclosed the emerging roles of circulating exosome-associated miRNAs in drug resistance (DR) of MM. To this end, the medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 37 publications
2
91
0
Order By: Relevance
“…Exosomes from bone marrow supernatant were obtained by using the Total Exosome Isolation Kit (from plasma) (Invitrogen, Carlsbad, CA, USA). Exosomes from the cell culture supernatant were obtained as reported (14). Nanoparticle tracking analysis (NTA) at VivaCell Biosciences with ZetaView PMX 110 (Particle Metrix, Meerbusch, Germany) was used to measure the exosome particle size and concentration.…”
Section: Exosomes Isolation and Nanosight Tracking Analysismentioning
confidence: 99%
“…Exosomes from bone marrow supernatant were obtained by using the Total Exosome Isolation Kit (from plasma) (Invitrogen, Carlsbad, CA, USA). Exosomes from the cell culture supernatant were obtained as reported (14). Nanoparticle tracking analysis (NTA) at VivaCell Biosciences with ZetaView PMX 110 (Particle Metrix, Meerbusch, Germany) was used to measure the exosome particle size and concentration.…”
Section: Exosomes Isolation and Nanosight Tracking Analysismentioning
confidence: 99%
“…miRs are small double-stranded RNAs with strong regulatory potential [44] and its differential abundance in cancer-derived EVs have been associated with the presence and aggressiveness of squamous cell carcinoma, prostate and bladder cancer, among others [22, 30, 34–36, 4555]…”
Section: Evs As Non-invasive Source For Biomarker Discoverymentioning
confidence: 99%
“…Circulating exosome‐related miRNAs were recently utilized as prognostic biomarkers to predict acquired or primary drug resistance, by comparing responsive and bortezomib‐resistant patients with MM. In fact, down‐regulation of four exosomal miRNAs, including miR‐17‐5p, miR‐20a‐5p, miR‐15a‐5p, and miR‐16‐5p were observed in the bortezomib‐resistant patients . As discussed before, miRNAs are implicated in bone metabolism and MM‐bone disease.…”
Section: Exosomes and MMmentioning
confidence: 76%
“…In fact, down-regulation of four exosomal miRNAs, including miR-17-5p, miR-20a-5p, miR-15a-5p, and miR-16-5p were observed in the bortezomib-resistant patients. 98 As discussed before, miRNAs are implicated in bone metabolism and MM-bone disease. Recently, Sun et al showed that exosomal miR-214 secreted by OCs is transferred into OBs, by EphA2/EphrinA2 molecules, through suppressing their activities.…”
Section: Exosomes and MMmentioning
confidence: 91%